Lettre de Monsieur le duc de Mayenne au roy : auec la response à icelle par sa Majesté. - Mayenne, Henri de Lorraine, duc de, 1578-1621.; Martin, Edme, 1618-1670 (A Paris : Chez Edme Martin, ruë S. Iacques, à l'enseigne de la Corne de Cerf, 1617)
"The Duc de Mayenne writes to the King and announces that an attempt has been made on his life. He implies that the attempt may have been instigated from his court."--French Political Pamphlets Digital Collection, Brigham Young University.
This edition not in Lindsay in Neu. Editions by other printers found in Lindsay, R.O. French political pamphlets, 1547-1648, entries 3945 and 3946.
Differs from signature A of the 14, [2] page printing by Edme Martin on page 5. The closing of the letter ends on the line above the signature: "tres-obeyssa[n]t & tres-fidelle seruiteur," and lacks the "& subiet" on the same line as "Mayenne".
Lacks the response from the king.
"Mayenne. De Soissons ce 11 ianuier 1617"--Page 5.
Title vignette; head-piece; initial.
Last [3] pages blank.
Keywords: Louis -- XIII, -- King of France, -- 1601-1643.; Mayenne, Henri de Lorraine, -- duc de, -- 1578-1621.; Louis -- XIII, -- King of France, -- 1601-1643.; Mayenne, Henri de Lorraine, -- duc de, -- 1578-1621.; 1610-1643; Politics and government; France; France -- Politics and government -- 1610-1643.; France -- History -- Louis XIII, 1610-1643 -- Pamphlets; Pamphlets -- France -- Paris -- Seventeenth century (dates CE).; History